Sport Science Publication of the International Tennis Federation (Coaching and Sport Science Review, 2010)
Maximise You - 10 Tips For Coach Well Being (Ann Quinn) Biomechanical Analysis of Stroke Production (Bruce Elliott) Player Development - 1993-2010 and Beyond (Doug MacCurdy) The State of Play: Coaching Persons with Disabilities (Janet A Young) Being a team captains (Steven Martens) Strength & Conditioning for Tennis - A 25 Year Journey (Mark Kovacs) Analysis of Strategy and Tactics in Tennis (Scott Over (ITF) and Peter O´Donoughue) Injury Prevention (Brian Hainline) Developments in coaches education (Frank van Fraayenhoven) New trends on tennis psychology and psychological training (Antoni Girod) Junior Development - Current Status and Future (Piotr Unierzyski) Periodisation in tennis (Machar Reid, Geoff Quinlan and Craig Morris) Player Welfare- ITF Initiatives to Enhance Safety and Welfare (Kathy Martin) Wheelchair Tennis in 2010 (Mark Bullock and David Sanz SPA) ITF Coaching and Sport Science Review: An Analysis of 17 Years - 50 Issues (Miguel Crespo and Scott Over)